Perbandingan Micronucleus dan Karyorrhexis pada Mukosa Lidah Perokok - Yolanda Yenolinsky; Yuktiana Kharisma; Ismet Muchtar Nur (Jurnal Riset Kedokteran, 2024)
Abstract. Although awareness of the negative health impacts of smoking is increasing, the prevalence of active smokers in Bandung City, especially in the neighborhood of the Islamic University of Bandung campus, remains high. The study was conducted as an observational study with a cross-sectional design, involving 20 smokers at Islamic University of Bandung. It is done by taking a peel of the mucous membrane and tongue and colored with coloring boardicolaou. Hail's research showed on the examination of the mucous membrane of the tongue revealed significant differences, especially in the number of micronucleus, as indicators of the genotoxic impact of tobacco compounds. Smokers have higher rates of cellular changes, such as micronucleus and cariorexis. The findings underscore the need for more effective interventions to reduce the prevalence of smoking in different groups of society, taking into account factors such as education and the type of work. The results provide a basis for the prevention of smoking-related diseases in the campus and the community in general. Abstrak. Meskipun kesadaran akan dampak negatif rokok terhadap kesehatan meningkat, prevalensi perokok aktif di Kota Bandung, terutama di lingkungan kampus Universitas Islam Bandung, tetap tinggi. Penelitian ini dilakukan sebagai studi observasional dengan rancangan cross-sectional, melibatkan 20 perokok di Universitas Islam Bandung. Dilakukan dengan mengambil apusan mukosa bukal dan lidah dan diwarnai dengan pewarnaan papanicolaou. Hail penelitian menunjukan pada pemeriksaan mukosa lidah mengungkapkan perbedaan signifikan, terutama pada jumlah micronucleus, sebagai indikator dampak genotoksik senyawa tembakau. Perokok memiliki tingkat perubahan sel yang lebih tinggi, seperti micronucleus dan karyorrhexis. Temuan ini menggarisbawahi perlunya intervensi lebih efektif untuk mengurangi prevalensi merokok di berbagai kelompok masyarakat, dengan mempertimbangkan faktor-faktor seperti pendidikan dan jenis pekerjaan. Hasil ini memberikan dasar untuk upaya pencegahan penyakit terkait merokok di lingkungan kampus dan masyarakat umumnya.